2015
DOI: 10.1007/s13592-014-0334-x
|View full text |Cite
|
Sign up to set email alerts
|

The density of feral honey bee (Apis mellifera) colonies in South East Australia is greater in undisturbed than in disturbed habitats

Abstract: -Apis mellifera is an important pollinator but is sometimes associated with adverse effects on natural ecosystems. We surveyed pairs of disturbed and undisturbed sites across three biomes in South East Australia. We used pheromone lures to trap drones, genotyped the drones to infer the number of colonies within flight range and then estimated colony densities using synthetic sampling distributions. Estimated colony densities ranged from 0.1 to 1.5 colonies km −2 and significantly lower in agricultural land rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 45 publications
0
40
3
1
Order By: Relevance
“…Despite the potential sampling error in calculating true colony density, our estimate for 2013 is similar to other studies in areas with suitable and unsuitable patches of colony nesting habitat, including surveys in Panama (4-7 colonies/km 2 , Boreham and Roubik 1987), New York (2.7 colonies/km 2 , Morse et al 1990), Mexico (6 colonies/km 2 , Ratnieks et al 1991), and Botswana (4.2 colonies/km 2 , McNally and Schneider 1996). Our observed colony density in 2013 was roughly one order of magnitude higher than the density reported by Arundel et al (2014) in Victoria, Australia (0.1-0.5 colonies/km 2 ), and was nearly two times higher than the highest density (3 colonies/ km 2 ) that Hinson et al (2015) reported for feral honey bees in undisturbed habitats in Southeastern Australia, however. Results from all these surveys confirm that different landscapes will accommodate different maximum colony densities depending on the biogeophysical properties of each habitat (Hinson et al 2015).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Despite the potential sampling error in calculating true colony density, our estimate for 2013 is similar to other studies in areas with suitable and unsuitable patches of colony nesting habitat, including surveys in Panama (4-7 colonies/km 2 , Boreham and Roubik 1987), New York (2.7 colonies/km 2 , Morse et al 1990), Mexico (6 colonies/km 2 , Ratnieks et al 1991), and Botswana (4.2 colonies/km 2 , McNally and Schneider 1996). Our observed colony density in 2013 was roughly one order of magnitude higher than the density reported by Arundel et al (2014) in Victoria, Australia (0.1-0.5 colonies/km 2 ), and was nearly two times higher than the highest density (3 colonies/ km 2 ) that Hinson et al (2015) reported for feral honey bees in undisturbed habitats in Southeastern Australia, however. Results from all these surveys confirm that different landscapes will accommodate different maximum colony densities depending on the biogeophysical properties of each habitat (Hinson et al 2015).…”
Section: Discussioncontrasting
confidence: 45%
“…Results from all these surveys confirm that different landscapes will accommodate different maximum colony densities depending on the biogeophysical properties of each habitat (Hinson et al. ).…”
Section: Discussionmentioning
confidence: 59%
“…Table S1 provides estimates of honey bee colony densities derived from direct survey and drone trapping surveys based on Hinson et al (2015). These studies show that the density of colonies varies hugely with the environment and assessment technique.…”
Section: Results To Datementioning
confidence: 99%
“…Males can be sampled from an area either by an aerial trap baited with a pheromone lure (Kraus et al, 2005b;Moritz et al, 2007;Jaffé et al, 2010;Arundel et al, 2012;Hinson et al, 2015) (see the Sampling methods section below and Fig. Males can be sampled from an area either by an aerial trap baited with a pheromone lure (Kraus et al, 2005b;Moritz et al, 2007;Jaffé et al, 2010;Arundel et al, 2012;Hinson et al, 2015) (see the Sampling methods section below and Fig.…”
Section: Population Genetic Methods For Assessing Colony Densitiesmentioning
confidence: 99%
See 1 more Smart Citation